(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
Under the umbrella of Book Science, research in publishing has a long tradition in Lithuania and is today perceived as an independent branch of scholarship within the Communication and Information Sciences. On the basis of original sources, the aim of this article is to analyse the work conducted by the Institute of Book Science and Documentation of Vilnius University in implementing third level publishing studies (meaning PhD level) and to outline the merits, weak points, opportunities and threats in the planning of further training of scholars within this particular branch. The key research sources are documentation governing doctoral studies in Lithuania, at Vilnius University and the field of Communication and Information Sciences, as well as Communication and Information Sciences doctoral study programmes and descriptions of disciplines, PhD student lists, students’ publication indexes and different archival documents of doctoral studies at the Institute of Book Science and Documentation of the Faculty of Communication of Vilnius University.